Low‐complexity energy‐efficient power allocation scheme for distributed MISO system with beamforming. Issue 24 (1st November 2019) - Xu, Weiye; Yu, Xiangbin; Teng, Tao
Abstract : This letter investigates the energy efficiency (EE) optimisation of a distributed multiple‐input single‐output (D‐MISO) system, and a suboptimal power allocation (PA) scheme with low complexity is developed for D‐MISO system with beamforming. Different from the existing optimal PA scheme that needs iterative calculation, the developed scheme can provide closed‐form PA and no iteration is required. Using the Cauchy–Schwarz inequality, the upper bound of EE is first obtained, and then the optimised objective function is formulated subject to a set of power budget constraints. By maximising this upper bound, a suboptimal PA scheme for the system is derived, and closed‐form PA coefficients are attained. Interestingly, it is found that the proposed scheme has the same general form of PA as the optimal scheme. Numerical results verify the effectiveness of the proposed scheme, it can achieve the EE performance very close to that of the existing optimal scheme due to better approximation, but it has lower complexity than the latter.